Knowledge of Nurses in Using Critical-Care Pain Observation Tools to Assess Pain of Unconscious Patient in Intensive Care Unit - Barkah Waladani; Endah Setianingsih; Margo Sutrisno; Syamsul Bahri (Babali Health, 2022)
Introduction: In the critical nursing area, many intubated patients are unable to communicate to indicate the level of pain felt. Assessing the characteristics of pain, especially in patients with mechanical ventilation is a major nursing intervention that requires nursing knowledge. The examination of the CPOT pain scale was certainly accompanied by the knowledge that must be possessed by the nurse when going to conduct a pain assessment in patients who were not able to express pain verbally in the ICU, so as to provide appropriate intervention and help assess the patient's pain response non-verbally. The purpose of this study was to determine the knowledge of nurses in using the Critical-care Pain Observation Tool in assessing pain. Methods: This study used a quantitative descriptive research method, with total sampling. Samples were taken by 72 respondents. Results: The results obtained 14 respondents with good knowledge, 26 respondents with enough knowledge, and 32 respondents with less knowledge. Conclusion: The conclusion is that the knowledge of nurses in using the Critical-care Pain Observation Tool in assessing pain is poor knowledge. The recommendation for this research is to provide knowledge related to pain assessment using CPOT with education.